2015
DOI: 10.1179/1743284714y.0000000712
|View full text |Cite
|
Sign up to set email alerts
|

Melting of multipass surface tracks in steel incorporating titanium carbide powders

Abstract: Overlapping tracks were processed by melting preplaced titanium carbide (TiC) powder on steel surfaces using a tungsten inert gas torch. The tracks produced ~1.0 mm melt depth free from cracks, but occasional pores were observed. The microstructure consisted of unmelted and partially melted TiC particulates together with reprecipitated TiC particles, which were prominent in tracks processed in the initial stage. A greater number of reprecipitated globular and cubic TiC particles were observed in tracks process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…These types of TiC distribution and segregation have also been reported in laser processed MMC coatings on titanium surfaces 7 and TIG torch processed coatings on titanium and steel surfaces. 21,27,[32][33][34][35] TiC precipitates of globular, cubic and flower morphologies were seen in many overlapping tracks, but were not uniformly distributed in the melt microstructures. Similar morphologies of TiC precipitates were also reported in single track composite coatings.…”
Section: Microstructurementioning
confidence: 99%
“…These types of TiC distribution and segregation have also been reported in laser processed MMC coatings on titanium surfaces 7 and TIG torch processed coatings on titanium and steel surfaces. 21,27,[32][33][34][35] TiC precipitates of globular, cubic and flower morphologies were seen in many overlapping tracks, but were not uniformly distributed in the melt microstructures. Similar morphologies of TiC precipitates were also reported in single track composite coatings.…”
Section: Microstructurementioning
confidence: 99%
“…More recently, a TIG torch technique has been explored for the surface modification of steels as a much cheaper option to lasers [5][6][7][8]. Previous studies have shown that the hardness of low alloy steels increased significantly when TiC in the form of powder, was incorporated through laser cladding [8] and the TIG melting technique [9][10][11].The development of improved wear resistance through the incorporation of SiC particles to produce metal matrix surface composites is well established in aluminum and titanium alloys by laser surface engineering [12][13][14].With the exception of work by Terry and Chinyamakobvu [15],who studied the effect of an addition of SiC particles on the wear properties of steel, little attention has been paid to using SiC particles in iron and steels for this purpose. Majumdar et al [16], attempted to develop a compositionally gradient SiC dispersed phase to improve the wear properties of mild steel, through laser cladding.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when a number of overlapping tracks are laid down to cover the surface, differences in microstructures have been reported to produce changes in hardness through the melt depth. For example, temperature increases greater than 500°C have been recorded between the first and final tracks for both titanium alloys [11,12] and steels [13,14]. These changes can also influence the surface roughness.…”
Section: Introductionmentioning
confidence: 99%